Bundling Governance: Finance versus Institutions in Private Investment Promotion - Simplice Asongu; Enowbi Batuo; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2015)
Purpose – The study extends the debate on finance versus institutions in the promotion of investment documented by Acemoglu and Johnson (2005), Ali (2013) and Asongu (2014). We assess the effects of various components of governance on private investment, notably: political, economic and institutional governances. Financial indicators of depth, allocation efficiency, activity and size are used. Design/methodology/approach – An endogeneity robust dynamic system GMM estimation technique is employed. Principal component analysis is also employed to reduce the dimensions of governance variables. The empirical evidence is based on 53 African countries for the period 1996-2010. Findings – The findings provide support for the quality of governance as a better determinant of private investment than financial intermediary development. Moreover, the evidence of finance and governance as substitutes in their impact on investment implies that good governance fuels private investment and this positive impact is stronger in nations with less developed financial systems. This finding is consistent with Ali (2013) and contrary to the results of Asongu (2014c). Practical implication – Policy measures for fighting involuntary and voluntary surplus liquidities are discussed. The paper provides additional support for the need of strengthening governance institutions to promote investment on the one hand and fighting financial allocation inefficiency by mitigating surplus liquidity issues on the other hand. Originality/value – The paper extends the debate on the substitution of finance and institutions in the promotion of private investment.
Keywords: G20; G24; E02; P14; O55; 330; Finance; Institutions; Investment: Property Rights; Africa